Performance analysis and techno-economic evaluation of 300 MW solar-assisted power generation system in the whole operation conditions. (15th April 2020) - Shagdar, Enkhbayar; Lougou, Bachirou Guene; Shuai, Yong; Anees, Junaid; Damdinsuren, Chimedsuren; Tan, Heping
Highlights: SAPG system exhibited higher operating performance with many ecological advantages. Higher techno-economic indices can be obtained when the high potential steam extraction system is replaced by solar energy. SAPG system is strongly affected by the variation of DNI compared to the power output. The off-design regime can be reduced more fuel and CO2 emission compared to the design regime. SAPG system can significantly contribute to environmental pollution reduction. Abstract: Integrating solar energy into conventional thermal power plant is one of the most efficient approaches of solar energy utilization for power generation purposes with minimum pollutants in near and midterm. In this paper, we have investigated the integration of solar energy with 300 MW coal-fired thermal power plant by replacing the first high-pressure heater (HPH#1) with parabolic trough collector type solar field. Our study aims to analyze the performance of 300 MW solar-assisted power generation (SAPG) system at different operation conditions in terms of techno-economic and ecological indices. The SAPG system is investigated for both fuel-saving (FS) and power-boosting (PB) operation modes. We have observed the reduction of 0.19 kg/kWh and 391 kJ/kWh in specific steam consumption and specific heat consumption, respectively in SAPG system. Moreover, the specific equivalent fuel consumption is decreased by 14.92 g/kWh. In SAPG system with FS mode, coal consumption is reduced by 8.82 tons per hour compared to the base case whereas, for PB mode, power output is increased by 20 MW per hour compared to the base case. The possibility of an annual reduction of coal and CO2 emission is calculated as 32, 150 tons and 47, 030 tons respectively when SAPG system operates at nominal load. Considering the annual amount of reduced coal and pollutant emissions in the total system, SAPG system can significantly contribute to the reduction of pollutant emissions. Furthermore, the economic analysis estimates that the simple payback period and the LCOE are approximately 5.91 years and 0.13 USD/kWh respectively in design condition.